Writing jazz biography: race, research and narrative representation - Perchard, Tom (Popular Music History, 2007)
The historical biography has come to be viewed with suspicion by those who recognise that the genre’s literary emplotment and narrative demands can waylay the scholarly search for objective historical “truth”. This article explores these biographical narrative conventions and applications – and proposes new approaches to researching and writing within the biographical format – in the context of historical jazz studies. The piece begins by considering, with reference to several biographies of the saxophonist John Coltrane, both the ways that biographical narratives are constituted from disparate source materials and the ideological agendas and political problems that attend this creative act. The article argues that, in the course of doing biographical work, these issues might begin to be accounted for and dealt with by rethinking of the nature of historical-biographical “research”, and by way of hermeneutic, historical-dialogical method of the kind outlined by Hans-Georg Gadamer; with a theoretical approach delineated (and with reference to the author’s own experiences as a jazz biographer), the article goes on to engage with the processes and politics of this research stage, discussing oral history fieldwork and its textual representation, placing special emphasis on encounters of race so often inherent to jazz research and writing. Finally, the piece returns to the act of biographical writing itself, and outlines what, in light of the foregoing discussion, might be considered as new aims, values and strategies for the jazz biographical narrative, and perhaps for biography more generally.